STRATEGI PEMBELAJARAN KITAB FATH AL QARIB DALAM MENINGKATKAN PEMAHAMAN FIKIH DI MADRASAH DINIYAH AL ANWAR PACULGOWANG JOMBANG - Ima Mahmudah; Burhanuddin Ridlwan; Syamsuddin (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2019)
This article examines the learning strategies of the Fath al-Qarib Book as a way of conveying fikih material in learning in order santri is able to understand, translate or interpret, give examples, conclude, compare, explain, and solve a problem. This article is a case study with a qualitative approach. The result of this study is that in the learning process, santri carried out syawir (musyawarah) consisting of three santri, each of them got the task of reading books, translating (muradi), and explaining (mubayyin). With these such learning, santri are able to read, translate and explain fikih material in their own language. In that learning also they faced obstacles in concentration, implementation of syawir (deliberation), the ability of santri, and condition of the santri. Those learning are supported by the activities of deliberation (deliberation), motivation, and teacher support, and handbooks in learning